A particularly complex case of matricide by means of plastic bag suffocation: Case report. (July 2017) - Migliorini, Arnaldo Stanislao; Boracchi, Michele; Gentile, Guendalina; Maciocco, Francesca; Piccinini, Andrea; Zoja, Riccardo
A rare case of homicide with plastic bag suffocation is presented in which forensic genetic investigations were carried out on the inner surface of a plastic bag placed over the head of an elderly woman, bedridden after a stroke. The results obtained suggested that she had been murdered and hinted at the perpetrator of the crime. In fact, it emerged that biological traces left by the victim matched those of her principal caregiver, her psychotic daughter, who later confessed to the crime. The old woman also had a son affected by a serious illness, whose genetic profile was found on the same bag. In a later interview, he stated that his sister had tried to kill him too, thus confirming the genetic findings and allowing the investigators to hypothesise that the daughter had used the same means to try to kill him. Based on these results, the usefulness of forensic genetic testing when investigating complex plastic bag suffocation deaths is highlighted. This peculiar case deserves interest, since no murder of this kind has ever been reported in the Italian forensic literature.